2015
DOI: 10.1093/glycob/cwv010
|View full text |Cite
|
Sign up to set email alerts
|

4-O-Acetyl-sialic acid (Neu4,5Ac2) in acidic milk oligosaccharides of the platypus (Ornithorhynchus anatinus) and its evolutionary significance

Abstract: Monotremes (echidnas and platypus) retain an ancestral form of reproduction: egg-laying followed by secretion of milk onto skin and hair in a mammary patch, in the absence of nipples. Offspring are highly immature at hatching and depend on oligosaccharide-rich milk for many months. The primary saccharide in long-beaked echidna milk is an acidic trisaccharide Neu4,5Ac2(α2-3)Gal(β1-4)Glc (4-O-acetyl 3'-sialyllactose), but acidic oligosaccharides have not been characterized in platypus milk. In this study, acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…29) Apart from the structural diversity among mammals, milk oligosaccharides also appeared in monotreme species (platypus and echidna). 76) Urashima et al have claimed that the original function of milk oligosaccharides is the prevention of microbial infection (HMOs also work in that way) and that the roles of milk oligosaccharides have diversified later during evolution. 76) In a rare case of cross-kingdom symbiosis, humans and bifidobacteria might have succeeded in mutually exploiting HMOs as beneficial compounds, as deduced by the fact that the presence of type-1 chain-specific enzymes is limited to infant-gutassociated bifidobacteria and that only human milk is rich in type-1 chain oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…29) Apart from the structural diversity among mammals, milk oligosaccharides also appeared in monotreme species (platypus and echidna). 76) Urashima et al have claimed that the original function of milk oligosaccharides is the prevention of microbial infection (HMOs also work in that way) and that the roles of milk oligosaccharides have diversified later during evolution. 76) In a rare case of cross-kingdom symbiosis, humans and bifidobacteria might have succeeded in mutually exploiting HMOs as beneficial compounds, as deduced by the fact that the presence of type-1 chain-specific enzymes is limited to infant-gutassociated bifidobacteria and that only human milk is rich in type-1 chain oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Among detection strategies, histochemical staining has become a widely accepted technique for detecting O-acetylated Neu5Ac with information on site-specificity ( Table 2). Ravindranaths and co-workers, for instance, showed that radiolabeled, purified crab lectin from Cancer antennarius incubated with erythrocytes in Tris buffered saline bound to C 9 O-acetylated Neu5Ac using radiolabelled assays [51]. More recently, advances in using matrix-assisted laser desorption/ionization mass spectrometry (MALDI) combined with imaging software have enabled mapping of the localization of O-acetylation on gangliosides [52,53].…”
Section: Extraction and Detection Methods Of O-acetylated Neu5acmentioning
confidence: 99%
“…HE exhibits hemagglutination and receptor destroying activities and C 4 -O-acetylated Neu5Ac was defined as the major receptor determinant [81]. While influenza C virus recognizes C 9 -O-acetylated Neu5Ac, ISAV is selective for C 4 -O-acetylated Neu5Ac in receptor binding and destroying activities, despite known similarities to influenza C virus HE [51].…”
Section: Biological Implications Of C7-9 and C4 O-acetylated Neu5acmentioning
confidence: 99%
See 1 more Smart Citation
“…The display and functions of modified 4-O-Ac Sias in intrinsic cell processes are poorly understood. They have been previously identified using high-performance liquid chromatography (HPLC) analyses in certain tissues, blood proteins, and erythrocytes and within the cells of vertebrates of varied lineages, including horses and donkeys, guinea pigs, mice, and monotremes, and in many lineages of bony fish ( 14 , 22 26 ). They appear to be distributed in fewer species than the O-acetyl modifications on the Sia glycerol side chain.…”
Section: Introductionmentioning
confidence: 99%